Total atrioventricular block in patient with late onset acute inferior myocardial infarction - Kawilarang, Ken Christian; Hermawan, I. Kadek H.; Hartono, Febryanti (International Journal of Research in Medical Sciences, 2021)
TAVB is common complication of acute inferior myocardial infarction (AMI). Total atrioventricular block (TAVB) occurs when none of the impulses are conducted from atrium to ventricles and move independently without coordination. In our case, A 61-year-old woman came to the emergency room (ER) with chief complaint of general weakness and nausea without any other complaints since 4 days before going to ER. She had TAVB which is a complication of undiagnosed AMI due to silent ischemia. She didn’t get reperfusion therapy because of patient delay and limited resources. Pharmacological therapy had been given while awaiting implantation of temporary pacemaker (TPM). Two days after insertion, the heart rhythm returned to sinus rhythm, therefore permanent pacemaker implantation was not required. TAVB in AMI usually resolves spontaneously. Therefore, it is important to identify TAVB in AMI, so we can quickly diagnose and promptly treat the patient. Thus, it can reduce mortality and increase the probability of spontaneous resolution of TAVB, so physician practice management (PPM) insertion can be avoided.